Whole-Brain Functional Networks for Phonological and Orthographic Processing in Chinese Good and Poor Readers - Yang, Jing; Tan, Li Hai (Frontiers in Psychology, 2020)
The neural basis of dyslexia in different languages remains unresolved, and it is unclear whether the phonological deficit as the core deficit of dyslexia is language-specific or universal. The current functional magnetic resonance imaging (fMRI) study using whole-brain data-driven network analyses investigated the neural mechanisms for phonological and orthographic processing in Chinese children with good and poor reading ability. Sixteen good readers and 16 poor readers were requested to make homophone judgments (phonological processing) and component judgments (visual-orthographic processing) of presented Chinese characters. Poor readers displayed worse performance than the good readers in phonological processing, but not in orthographic processing. Whole-brain activation analyses showed compensatory activations in the poor readers during phonological processing and automatic phonological production activation in the good readers during orthographic processing. Significant group differences in the topological properties of their brain networks were found only in orthographic processing. Analyses of nodal degree centrality and betweenness centrality revealed significant group differences in both phonological and orthographic processing. The present study supports the phonological core deficit hypothesis of reading difficulty in Chinese. It also suggests that Chinese good and poor readers might recruit different strategies and neural mechanisms for orthographic processing.